Pelembagaan Perspektif Masyarakat Sasaq dalam Menjaga Potensi Kelautan di Kawasan Pesisir Teluk Jor Kabupaten Lombok Timur Nusa Tenggara Barat - Mey Susanti AS (Institut Ilmu Sosial dan Manajemen STIAMI, 2018)
The existence of mangrove forest ecosystems in coastal areas usually doesnt grows and develops by itself, but there are also other ecosystems, such as desert-seagrass ecosystems, algae and coral reefs, thus forming a vast and very complex ecosystem. The conditions like this are also found on the coast of Teluk Jor, Jerowaru, East Lombok Regency, West Nusa Tenggara. The absence of regulation of resource use is a problem in Teluk Jor which starts from the people's perception of marine and fisheries resources as public property, joint property or individual property. This studies aims to see the extent of the awiq-awiq role and the effectiveness of its implementation in developing the coastal community of Teluk Jor. The research method used is a qualitative method, with a phenomenological perspective. The results of the identification shows that awiq-awiq Teluk Jor is formed from local wisdom and community initiation to conserve the areas.